Principal Leadership Strategies in Accelerating the Adiwiyata Program: A Comparative Study at Public Elementary School Duren Jaya IV and Public Elementary School Aren Jaya VIII, Bekasi City - Mahrojah Mahrojah (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to examine and compare the leadership strategies of school principals in accelerating the Adiwiyata Program at State Elementary School Duren Jaya IV and State Elementary School Aren Jaya VIII, Bekasi City using a qualitative approach with a multi-site study design. State Elementary School Duren Jaya IV was selected as a school that successfully accelerated environmental achievements to the provincial level, while State Elementary School Aren Jaya VIII was chosen as a comparison school that faced challenges in environmental culture sustainability. The study focused on mapping the initial conditions of both schools, managerial tasks of school principals, the actual implementation of the four components of the Environmentally Caring and Cultured School Movement (PBLHS), and the impact of environmental school management on the effectiveness of the environmental movement in schools. Data collection was conducted through participatory observation of physical facilities, in-depth interviews with school principals and environmental coordinators, and documentation studies based on the POAC management instrument. The findings indicate that managerial tasks at schools implementing participatory transformation in State Elementary School Duren Jaya IV through innovation in “Waste Savings,” waste sorting, and budget allocation operated successfully in creating an ecological culture, which encouraged higher achievement at the provincial level. In contrast, managerial dysfunction at State Elementary School Aren Jaya VIII resulted in stagnation because of weak daily leadership control. The study concludes that environmental leadership has implications for environmentally oriented decision-making models in elementary schools to accelerate the Environmentally Caring and Cultured School Movement sustainably.